Gore Vidal snapshots in history's glare - Vidal, Gore 1925-2012 (Abrams, 2009)
"This book is Gore Vidal's visual memoir of his remarkable and famously well-lived life. In this collection of photographs, letters, manuscripts, and other selections from Vidal's vast personal archives, readers are escorted by one of America's wittiest insiders into the Kennedys' Camelot, as well as onto the set of Ben Hur, and into the private lives of Eleanor Roosevelt, Paul Newman, and Tennessee Williams, to name a few" -- inside cover.
Keywords: Vidal, Gore -- 1925-; Vidal, Gore -- 1925-2012; Geschichte 1900-2000; Authors, American -- 20th century -- Biography; Bildband; Biografie